PENGARUH INTELLECTUAL CAPITAL, LIKUIDITAS DAN FAKTOR LAINNYA TERHADAP NILAI PERUSAHAAN - Aletha, Vony; A. Mulyana, Ricky (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
Firm value reflects the level of a company’s success and the perception investors have toward the company. The purpose of this study is to examine several factors that can affect firm value such as intellectual capital, managerial ownership, profitability, tax avoidance, leverage, and liquidity. The object of this research includes all manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024. The sample was selected using the purposive sampling method and the data was analyzed using the multiple regression method. There are 91 companies with 273 data used as samples in this study. The results of this research indicate that the variable of profitability has a positive effect on firm value. A high level of profitability shows the company’s ability to manage its resources effectively to generate profit. Meanwhile, intellectual capital, managerial ownership, tax avoidance, leverage, and liquidity have no effect on firm value.